2021
DOI: 10.2147/cmar.s283746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intrafractional Motion in Head and Neck Cancer Between Two Immobilization Methods During Stereotactic Ablative Radiation Therapy by CyberKnife

Abstract: Purpose: Maintaining immobilization to minimize spine motion is very important during salvage stereotactic ablative radiation therapy (SABR) for recurrent head and neck cancer. This study aimed to compare the intrafractional motion between two immobilization methods. Patients and Methods: With a spine tracking system for image guiding, 9094 records from 41 patients receiving SABR by CyberKnife were obtained for retrospective comparison. Twenty-one patients were immobilized with a thermoplastic mask and headres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Kang CL et al. ( 19 ) also found that intra-fraction motion increases with increasing treatment duration, especially in the x-axis direction. Also, Kang CL et al.…”
Section: Discussionmentioning
confidence: 90%
“…Kang CL et al. ( 19 ) also found that intra-fraction motion increases with increasing treatment duration, especially in the x-axis direction. Also, Kang CL et al.…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, an investigation on the intra-fractional motion of HN cancer patients with the aid of an immobilization device (e.g., Orfit 5-point mask with shoulder extension and headrest cushion) reported a motion range of within 1 mm translation and 0.7 • rotation. 25 Secondly, an assessment study on the spot position uncertainty of scanning proton pencil beam reported an uncertainty range of within 1 mm for the maximum day-to-day variance for any given spot positions. 26 After simulating the CBCT-guided online APT for every treatment fraction by conducting the steps 3−10 of the proposed workflow,deformable image registration was performed to deform the corrected CBCT images to the planning CT images to accumulate the actual dose of the in-use plan (i.e., either the nominal plan if online adaptation was not triggered yet or the latest new plan) over the entire treatment course.…”
Section: Retrospective Simulation Studymentioning
confidence: 98%
“…Using a smaller setup margin for online adaptation was also suggested in multiple other studies on adaptive radiotherapy 37,38 A recent review paper by Huiskes et al on adaptive proton therapy in HN cancer noted that the majority of online adaption studies did not use any setup margin. 39 We would like to mention that our determina-tion of the 1.5 mm margin size was based on a study on intra-fractional motion of HN cancer patients 25 and a study on spot positioning uncertainty. 26 The optimal margin size for each individual patient needs further investigation in the future with the technology of online APT being in place.…”
Section: Ctv-highmentioning
confidence: 99%
“…After the introduction of 4DCT and the definition of ITV, the PTV is created with a smaller margin (5 mm) when expanded from the ITV, thus allowing more normal tissue sparing 32 . Nowadays, with advanced immobilization and IGRT techniques, we can confidently reduce the target within a couple of millimeters in the extra‐cranial disease sites such as head neck and spine 33,34 . Such margin reduction, coupled with the advancement in treatment planning optimization and dose calculation algorithm, provides our community a high conformal treatment plan quality and a precise dose deposition.…”
Section: Technology Development For Sabr In the Past 25 Yearsmentioning
confidence: 99%
“…32 Nowadays, with advanced immobilization and IGRT techniques, we can confidently reduce the target within a couple of millimeters in the extra-cranial disease sites such as head neck and spine. 33,34 Such margin reduction, coupled with the advancement in treatment planning optimization and dose calculation algorithm, provides our community a high conformal treatment plan quality and a precise dose deposition. With the introduction of multi-leaf collimators in the late 1990s, 35 we are moving from 2D dose calculation by hand [36][37][38] to 3D conformal dose calculation, 39 and now to inverse optimization approach, [40][41][42] offering a superior dosimetric sparing for healthy tissues via the modulation of the fluence map, i.e.…”
Section: Treatment Planning: the Power Of Optimization And Dose Calcu...mentioning
confidence: 99%